Identification of Drought Tolerant Recombinant Inbred Lines and Estimation of Genetic Diversity by Clustering and Multivariate Analysis in Wheat RILs Populations - Khare, Vikrant; Shukla, R. S.; Pandey, Suneeta; Singh, Sanjay (International Journal of Bio-resource and Stress Management, 2022)
The current experiments were carried out in alpha lattice design at the Seed Breeding Farm, Department of Plant Breeding and Genetics, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh state, India, during 2019-20 and 2020-21 crop seasons, using 236 RILs population. The aim of current experiment is to assessment of genetic diversity and identification of promising recombinant inbred lines for irrigated and restricted irrigated conditions through PCA and cluster analysis. The drought selection indices viz. Relative drought index, yield stability index, drought resistance index, mean productivity, stress tolerance index and yield index were performed from two year grain yield pooled data. The principal component analysis and cluster analysis were performed through drought selection indices. Drought selection indices viz. relative drought index, yield stability index, yield index were confirm strong positively associated with grain yield under restricted irrigated conditions while mean productivity, stress tolerance index and yield index were strong positively associated with grain yield under irrigated conditions. Moreover, high cluster mean, for grain yield under restricted irrigated condition with associated selection indices was confirmed by 77 inbred lines from cluster I. similarly 128 superior inbred lines were found for irrigated condition. The highest inter cluster distance was observed between cluster I and cluster III therefore the inbred line occupy by cluster I and cluster III were considered as most diverse lines and could be used in farther breeding program to achieve more recombination for drought tolerance.